Orthodox Christian Biblical Studies in Pursuit of Identity: The Role and Impact of Personal Research Practices - Sergiy Golovashchenko (Kyiv-Mohyla Humanities Journal, 2016)
The article explores the pursuit of identity in Ukrainian Orthodox biblical studies not only in liturgical, exegetical, moral, educational and apologetic dimensions, but also from the perspective of academic criticism. It reviews the key points of this process, as discovered in the legacy of prominent representatives of the Kyivan biblical study tradition. Governmental influence on the Church’s educational policies, balancing between loyalty to the Orthodox tradition and Western biblical criticism, is among the factors that have shaped biblical studies, this issue being explored in the article. Historical milestones of biblical studies are presented, as is the research of prominent Kyivan scholars. Considering all these aspects and other crucial issues, the conclusion shows what makes the Kyivan tradition of biblical studies unique and of lasting importance.